Does an elbow arthrogram change management after closed reduction of mildly displaced lateral condyle fractures in children?. Issue 1 (24th September 2020) - Swarup, Ishaan; Chan, Calvin; Mehta, Nishank; Lawrence, John T.
Abstract : The purpose of this study was to investigate whether an elbow arthrogram after closed reduction and percutaneous fixation of lateral condyle fractures results in a change in surgical management. This is a retrospective review of lateral condyle fractures managed with closed reduction and percutaneous fixation followed by an elbow arthrogram at our institution between 2008 and 2019. Chart and radiographic review was performed and operative notes were reviewed to determine rates of subsequent intervention after arthrogram. Descriptive statistics were used to summarize the data. This study included 47 patients. The majority of patients were male (34 patients, 72%), and the mean age at time of injury was 5.5 ± 2.6 years. The mean radiographic displacement was 2.6 mm (range 0.8–6.9 mm). All fractures were managed by fellowship-trained pediatric orthopaedic surgeons with an average of 10.5 years of experience (range 0–32 years). Fractures were stabilized with percutaneous pins in 44 patients (94%) and percutaneous screws in three patients (6%). No patients had subsequent changes in management after an elbow arthrogram. There were no complications related to performance of the arthrogram. Closed reduction and percutaneous fixation is often indicated for mildly displaced lateral condyle fractures. Articular reduction after percutaneous fixation is commonly assessed using an elbow arthrogram; however, it did not change surgical management in any case reviewed over the 10-year study period. While there seems to be little risk of performing an arthrogram, the clinical utility should be further evaluated.